2020
DOI: 10.1186/s12894-020-00627-0
|View full text |Cite
|
Sign up to set email alerts
|

Early upregulation of AR and steroidogenesis enzyme expression after 3 months of androgen-deprivation therapy

Abstract: Background: Androgen deprivation therapy (ADT) is a standard treatment for advanced prostate cancer (PCa). However, PCa recurrence and progression rates during ADT are high. Until now, there has been no evidence regarding when progression begins. This study evaluated the gene expression of intraprostatic androgen receptor (AR) and steroidogenic enzymes in the early stages of ADT. Methods: Prostate tissue samples were taken from PCa patients with urinary retention who received ADT (ADT-PCa; n = 10) and were fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…SRD5A2 converts testosterone to dihydrotestosterone, which activates ARs 53,54 . SRD5A2 expression was significantly higher among patients with high-grade PCa vs. those with low-grade PCa 55,56 . In our previous study, we reported that the validated SNP-SNP interaction pairs of MMP16-EGFR, MMP16-ROBO1, and MMP16-CSF1 were significantly associated with PCa aggressiveness and that EGFR is the hub of these interactions 13 .…”
Section: Discussionmentioning
confidence: 85%
“…SRD5A2 converts testosterone to dihydrotestosterone, which activates ARs 53,54 . SRD5A2 expression was significantly higher among patients with high-grade PCa vs. those with low-grade PCa 55,56 . In our previous study, we reported that the validated SNP-SNP interaction pairs of MMP16-EGFR, MMP16-ROBO1, and MMP16-CSF1 were significantly associated with PCa aggressiveness and that EGFR is the hub of these interactions 13 .…”
Section: Discussionmentioning
confidence: 85%
“…However, in this study, there was no relationship between BGN expression and AR status (Figure S2). Furthermore, AR is known to be mutated by hormone therapy 27,28 . Thus, the AR may have been mutated during hormone therapy, but we were unable to determine whether the AR in the cases were mutated or not.…”
Section: Discussionmentioning
confidence: 92%
“…Variations in hormonal levels provoke adaptations in expression and activity of Estrogen and Androgen Receptors [86,87,88,89,90,91]. Estrogen deprivation has been shown to lead to ER oversensitisation, whereas constant activation of ERs to desensitisation [88,90].…”
Section: Diagnosis and Syndrome Provocationmentioning
confidence: 99%
“…The mechanisms behind the adaptations Similar reorganisation is known to occur after changes in the hormonal environment through other pathways. The removal of the gonads, perinatal exposure to sex hormones and the hormonal increases during puberty, all cause an abruptly altered hormonal environment, which subsequently leads to changes in receptor expression [84,86,87]. For example, pubertal emergence of sexual behaviour is induced by increased gonadal production and accompanied by synaptic reorganisation of the amygdala.…”
Section: • An Increase In Shbg Levelsmentioning
confidence: 99%